Sosialisasi Bahaya Penyalahgunaan Narkoba bagi Generasi Muda dan Penanggulangannya di Desa Naumbai: Socialization and Interventation The Dangers of Drugs Abuse for Young Generation - Henni Noviasari; Rizwan Tubagus; Andini Sekarwangi; Salsa Bila Annisa Putri; Zahwa Zulgaheni; Lisa Putri Amalia; Agnesa Dirgahayu Gustiadinda; Sulistia Wati; Emi Safitri; Rudy Kurniawan; Muhammad Effendi (BADAN PENERBIT STIEPARI PRESS, 2022)
Teenagers are the most important heritage that determines the future. It is well known teenagers needs guidance in ensuring their physical and mental growth. Drug abuse is not a fundamental problem in the community, but has become a very complex problem that requires prevention and an active community role that is carried out consistently and professionally. Circulation and abuse of drugs currently occurs not only in big cities in Indonesia, but also in villages. The method of application in this activity is by lecture and question and answer. This community service activity method uses the seminar method. The socialization was held on August 9, 2022 in the Naumbai Village Office Hall attended by a set of villages, Naumbai Village youth and Indra Wahyudi as BNN counselors as presenters. In the material, it was emphasized that various important points will occur if we avoid from drugs and how to deal it.